2017
DOI: 10.3945/jn.116.240028
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Regression Models for Adjustment of Iron Status Biomarkers for Inflammation in Children with Moderate Acute Malnutrition in Burkina Faso

Abstract: Cichon, B.; Ritz, C.; Fabiansen, C.; Christensen, V.B.; Filteau, S.; Friis, H.; Kstel, P. (2016)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 37 publications
1
17
1
Order By: Relevance
“…Physical examinations found 72 % had clinical symptoms (fever, malaria, upper and lower respiratory tract infections and diarrhoea) and more than 24 % had a CRP concentration >10 mg/l and 66 % an AGP concentration >1 g/l. In spite of the high proportion with clinical symptoms, internally calculated CF for ferritin did not significantly differ from those calculated for all children in our meta-analysis (8) . However, the authors concluded that 'regression analysis is preferable to the CF approach when adjusting serum ferritin for inflammation as it accounts for severity of inflammation and morbidity, however, in clinical settings the use of the meta-analysis CF may be appropriate'.…”
contrasting
confidence: 81%
See 1 more Smart Citation
“…Physical examinations found 72 % had clinical symptoms (fever, malaria, upper and lower respiratory tract infections and diarrhoea) and more than 24 % had a CRP concentration >10 mg/l and 66 % an AGP concentration >1 g/l. In spite of the high proportion with clinical symptoms, internally calculated CF for ferritin did not significantly differ from those calculated for all children in our meta-analysis (8) . However, the authors concluded that 'regression analysis is preferable to the CF approach when adjusting serum ferritin for inflammation as it accounts for severity of inflammation and morbidity, however, in clinical settings the use of the meta-analysis CF may be appropriate'.…”
contrasting
confidence: 81%
“…The meta-analysis studies were originally designed to be done on apparently healthy subjects with mild inflammation and correlations between the biomarkers and the APP would therefore be poor. The observations of Diana et al (1) and Cichon et al (8) suggest that some subjects with more severe inflammation can be included without seriously altering the CF obtained by meta-analysis. In the studies of Diana, Cichon and the BRINDA reports regression analysis produced greater corrections than the CF for all biomarkers studied.…”
mentioning
confidence: 99%
“…These findings were strengthened by the large sample size of the data set compared with in previous studies with similar findings (911). sTfR has been considered by many researchers as a potentially useful biomarker in settings where there is a high prevalence of inflammation because (unlike ferritin) it is not an APP and, therefore, is thought to not (28) or inconsistently (29) be influenced by inflammation. Notwithstanding, we showed that sTfR has a weak but consistent relation with AGP concentrations, which is associated with a lower prevalence of iron deficiency on the basis of measurements of sTfR, thereby indicating the need to apply adjustments for inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were frozen and thawed only once before analysis. As previously described, SF data were corrected for inflammation using a linear model with CRP, AGP, and morbidity (malaria, lower respiratory tract infections, and history of fever; Cichon et al, ). Malaria ( Plasmodium falciparum ) was diagnosed from venous blood using a rapid diagnostic test (SD Bioline Malaria Ag Pf).…”
Section: Methodsmentioning
confidence: 99%